Cardioprotective and Hepatoprotective Potential of Silymarin in Paracetamol-Induced Oxidative Stress - Bogdan Okiljević; Nikola Martić; Srđan Govedarica; Bojana Andrejić Višnjić; Milana Bosanac; Jovan Baljak; Branimir Pavlić; Isidora Milanović; Aleksandar Rašković (MDPI AG, 2024)
Silymarin, derived from Silybum marianum, has been used in traditional medicine for various ailments. In this study, the cardioprotective and hepatoprotective effects of silymarin against paracetamol-induced oxidative stress were examined in 28 male Swiss Webster mice, divided into four groups and treated for 7 days (via the oral route) with (a) saline 1 mL/kg (control group), (b) saline 1 mL/kg + single dose of paracetamol 110 mg/kg on the 7th day; (c) silymarin 50 mg/kg; and (d) silymarin 50 mg/kg + single dose of paracetamol 110 mg/kg on the 7th day. In vitro and in vivo antioxidant activity together with liver enzyme activity were evaluated. Histopathological and immunohistochemical assessment was performed. Silymarin mitigated paracetamol-induced liver injury by reducing oxidative stress markers such as lipid peroxidation and restoring antioxidant enzyme activity. Silymarin treatment resulted in a significant decrease in liver enzyme levels. Reduced necrosis and inflammatory infiltrate in liver tissues of silymarin-treated groups were detected as well. Immunohistochemical analysis demonstrated reduced expression of inflammatory markers (COX2, iNOS) and oxidative stress marker (SOD2) in the liver tissues of the silymarin-treated groups. Similar trends were observed in cardiac tissue. These results suggest that silymarin exerts potent hepatoprotective and cardioprotective effects against paracetamol-induced oxidative stress, making it a promising therapeutic agent for liver and heart diseases associated with oxidative damage.